PEREMPUAN DALAM LINTAS SEJARAH PERIWAYATAN HADIS - Bin Junaid, Junaid (PSW, 2012)
Hadith as a second source of Islamic teachings derived from narrators who were honest, fair and intelligent and its sanad is continuous. The narrators were male and female. Many narrators of hadith, especially the females (for example; Aisyah binti Abu Bakar Ashiddiq, Amrah binti Abdurrahman, and Hafsah binti Sirin), had direct in volvement and important role in the transmission of hadith of the prophet (pbuh). All of them have been enshrined in the books of hadith that are famous among the scholars of hadith.